Peningkatan Hasil Belajar Mawaris Melalui Pembelajaran Kooperatif Tipe Jigsaw - Tu Ramadhan (Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia., 2019)
The learning of Islamic Religious Education (PAI) in the class is less activity of the students because the learning strategy is dominated by the teacher, and there is no varied learning strategy, then the choice that can be done to solve this problem is with the use of cooperative type jigsaw in learning subjects Islamic Religious Education as well as conducting classroom action research. This study aims to find out how the activities of teachers and students in learning subjects Islamic Religious Education (PAI) discussion of inheritance with the use of cooperative type jigsaw on twelve students, Natural Science State High School one Kutamakmur, and to find out how to improve learning outcomes. This research uses a qualitative approach with the class action research method (PTK) and using data collection instrument through observation, test, diary, documentation and analyzed by reducing data, describe and conclude. And the subject of the research is the teacher of Islamic Religious Education who teaches mawaris material through the cooperative strategy of jigsaw type and students of class XII IPA.1 SMA Negeri 1 Kutamakmur academic year 2016/2017 second semester of 25 students. The results showed an increase: (1) In the first cycle of teacher activity 52%, then increased to 70% in cycle II, and the third cycle increased to 84%, (2) Student activity in the first cycle was 47%, then increased in cycle II to 68%, and on the third cycle increased to 83%, (3) student learning outcomes in cycle I was 10 students completed (40%), then in cycle II increased 16 students complete (64%), and cycle III increased to all students complete (100%).